The Cambridge companion to biblical wisdom literature - Dell, Katharine; Millar, Suzanna; Keefer, Arthur (Cambridge companions to religion, 2022)
Study of the wisdom literature in the Hebrew Bible and the contemporary cultures in the ancient Near Eastern world is evolving rapidly as old definitions and assumptions are questioned. Scholars are now interrogating the role of oral culture, the rhetoric of teaching and didacticism, the understanding of genre, and the relationship of these factors to the corpus of writings. The scribal culture in which wisdom literature arose is also under investigation, alongside questions of social context and character formation. This Companion serves as an essential guide to wisdom texts, a body of biblical literature with ancient origins that continue to have universal and timeless appeal. Reflecting new interpretive approaches, including virtue ethics and intertextuality, the volume includes essays by an international team of leading scholars. They engage with the texts, provide authoritative summaries of the state of the field, and open up to readers the exciting world of biblical wisdom.